MDG Achievements, Determinants and Resource Needs : What Has Been Learnt? - Lay, Jann (2012)
This paper reviews the effectiveness and efficiency of key policy instruments for the achievement of the Millennium Development Goals (MDG). Based on a simple cross-country regression analysis, the paper argues that average Millennium Development Goal progress is likely to be too slow to meet education and health sector targets in a number of developing countries. The paper further shows that MDG achievement can be described by a transition path with declining rates of progress. More detailed analysis reveals that the transition toward universal primary school enrollment in poor countries with low initial enrollment has accelerated considerably in the more recent past. The main part of the paper then focuses on the role of demand versus supply-side factors in social service utilization in education and health. The review arrives at the following rules of thumb that reflect some of the key determinants of achievement of the Millennium Development Goals: First, specific single policy interventions can have a considerable impact on social service utilization and specific human development outcomes. For example, improving access to basic health services, in particular to vaccination, has been a key factor in reducing child mortality rates in a number of very poor countries. Second, demand-side policies have proved extremely effective, for example in raising school enrollment and attainment levels. However, there may be more scope for targeting the demand-side in the health sector. Third, policy effectiveness and efficiency are highly dependent on initial conditions and the specificities of the respective policy. Fourth, complementarities between MDG targets, in particular social service utilization, are likely to be very important.